Assessment of Childbirth Fear Associated with Childbirth Satisfaction among Pregnant Women in Al-Nasiriyah City - Hanadi Ali Mahnoosh, Sarab Nasr Fadhil (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The fear of childbirth (FOC) is a common problem that affects a woman’s emotional health, preparation for childbirth, and the outcome of labor resulting in more intense and prolonged labor. In addition, this intense fear of childbirth supports an elective caesarean section. AIMS: To assess the childbirth fear associated with childbirth satisfaction among pregnant women at Al-Haboubi Hospital in Nasiriyah city. To explore the effect the childbirth fear associated with childbirth on women’ childbirth satisfaction. To find out the relationship childbirth fear and women’s sociodemographic and reproductive data. Methodology: A descriptive correlational design is conducted at Al-Haboubi Hospital in AL-Nasiriya city to assess the childbirth fear associated with childbirth satisfaction among pregnant women and explore its effect on women’ childbirth satisfaction. from 1st of October 2021 to 1st of April, 2022. The researcher designed the questionnaire to measure the purpose of the study. A convenient sample was selected consecutively from (100) pregnant women for an interview between the researcher and the pregnant woman before giving birth. In addition, communication is done by telephone after the birth for two weeks, and the discussion is conducted in the maternity hall. The data collected by use a questionnaire, which consists of four parts: the first part includes the social characteristics: the second part includes reproductive characteristics: the third part consists of the childbirth fear and the fourth part include the Mackey childbirth satisfaction scale. The information was analyzed in this study by using a statistical package for the social science program (IBM SPSS) version 24.0. Results: The results showed that pregnant women have an average age of 30.31±7.598 years. (43%) have at least (3 - 4) pregnancies , (25%) are at second delivery, (58%) "no have abortion" .(77%) at the high level of childbirth fear, there is a significant difference between fear of childbirth with age and educational level (p-value=0.028 and 0.038), respectively ,and there are significant differences between fear of childbirth with para, gravida, and the number of lived children at (p-value=0.002, 0.008, and 0.023), respectively. Conclusion: The study found that childbirth fear among pregnant women with a high level. Although of that the study found no has any effect on childbirth satisfaction. In addition, the study found a statistical difference between childbirth fear and some socio-demographic and reproductive characteristics Recommendations: Study findings and conclusions have led researchers to recommend the health care institutions to develop support plans and open a special mental health section to reduce the fear that pregnant women face from natural childbirth.